COMBINATION TREATMENT FOR ANTERIOR FOOT DEFORMITIES VIA RECONSTRUCTIVE AND JOINT-SPARING SURGERY IN PATIENTS WITH RHEUMATOID ARTHRITIS - Ya B Khrennikov; V P Pavlov (Научно-практическая ревматология, 2011)
Objective: to define the role and place of joint-sparing surgical interventions into the anterior foot in patients with rheumatoid arthritis (RA). Subject and methods. Eighty-six patients, the majority (n = 84) of young and middle-aged women, mainly with minimal disease activity, late-stage RA, and moderate limitation of functional capacity were examined and treated. One hundred and thirty arthrodeses of the first metatarsophalangeal joint (MPJ), 80 resections of the heads of the second-to-fifth metatarsal bones, and 58 Weil osteotomies were performed. Results. The American Orthopaedic Foot and Ankle Society (AOFAS) scale was used to assess arthrodesis of the first MPJ and resection of the second-to-fifth metatarsal bones (n = 141). This comparison shows higher scores for the operated limb in the postoperative period, but these changes cannot suggest the complete function of the feet operated on. Arthrodesis of the first MPJ and Weil osteotomy of the second-to-the first metatarsal bones were assessed by the AOFAS scale (n = 141). While assessing this surgical technique versus the previous method, there was an increase in scores for the second-to-fifth toes to almost normal values, which is in favor of the practically complete function recovery in the feet operated on. Conclusion. The Weil-osteotomy group showed the preservation and partial salvage of osteotomized heads, which promoted the recovery of swinging function of the foot. The new procedures made it possible to prevent recurrent valgus and hammer toe deformities and callus formation in the late postoperative period, to improve quality of life, and to reduce the time of rehabilitation and the length of hospital stay.